Synthesis of New Indole-Pyrazole linked Isoxazoles as Potent Antibacterial and Antibiofilm Agents - Reddycherla, Venkatesh; Chennakesavulu, K.; Reddy, G. Ramanjaneya; Reddy, R. Bhaskar (Asian Journal of Chemistry, 2026)
A series of new indole-pyrazole-linked isoxazole hybrids (5a-o) were synthesized using Cu(I)-catalyzed 1,3-dipolar cycloaddition and assessed for antibacterial and antibiofilm activities against methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Staphylococcus aureus (VRSA) pathogens. Biological evaluation showed that the dihalogenated derivatives, particularly 3,5-dichloro (5g) and 2,4-dichloro (5i), exhibited pronounced antibacterial activity comparable to dicloxacillin. Both compounds substantially inhibited biofilm formation. Molecular docking studies against penicillin-binding protein (PDB ID: 1MWT) supported the experimental findings, with favourable binding interactions and high predicted affinity. Structure-activity relationship analysis indicated that dichloro substitution enhanced antibacterial potency. These hybrid compounds may serve as potential candidates for further investigation against resistant Staphylococcus aureus infections.